2011
DOI: 10.1159/000329868
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Haptoglobin and CD163 Are Functional Immunoregulatory Elements in the Human Lung

Abstract: Background: The acute-phase protein haptoglobin (Hp) and its receptor CD163 serve as immunomodulators and possess anti-inflammatory besides antioxidant functions. Objectives: To further understand the role of the recently described pulmonary Hp (pHp) and its receptor CD163 in case of inflammation and infection, pHp and CD163 were investigated on mRNA and protein level to gain insight into the cellular events taking place upon stimulation with the inflammatory mediators LPS, Pam3, cytokine IL-6 and dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…CD163 may function as a pulmonary defense element, as suggested by its local expression in the lungs, and its secretion during lung infection and as part of inflammatory respiratory responses (98). Cell surface expression of CD163 on alveolar macrophages is reduced in human subjects with asthma, which suggests that CD163 may participate in the regulation of airway inflammatory responses in the lung (85).…”
Section: Functions Of Macrophages and Potential Role Of Cd163 In Asthmamentioning
confidence: 99%
“…CD163 may function as a pulmonary defense element, as suggested by its local expression in the lungs, and its secretion during lung infection and as part of inflammatory respiratory responses (98). Cell surface expression of CD163 on alveolar macrophages is reduced in human subjects with asthma, which suggests that CD163 may participate in the regulation of airway inflammatory responses in the lung (85).…”
Section: Functions Of Macrophages and Potential Role Of Cd163 In Asthmamentioning
confidence: 99%
“…However, this mutation did not associate with other infectious endpoints, and since the finding was based on a relatively low number of individuals it could represent a chance finding rather than a real phenomenon. On the other hand, studies support that MARCO [28,29] and other scavenger receptors [28,30,31,32] could be related to sepsis. The in vivo expression of MARCO is normally restricted to distinct populations of macrophages in the spleen and lymph nodes in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the plasma protein haptoglobin (Hp) is also synthesized and expressed in the human lung [1]. We described expression of Hp-protein in Lung cancer (mainly in Adenocarcinomas of the lung), Alveolar Epithelial Cells type II (AECII), alveolar macrophages and bronchial epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…Cell specific synthesis of pHp was addressed by RNA-in situ hybridization, which revealed pHp transcription in AECII and alveolar macrophages [1]. A possible secretion of pHp by pulmonary cells has been addressed utilizing human lung explants and A549 cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation